A Holistic Approach to Fishery Management: Evidence and Insights from a Central Mediterranean Case Study (Western Ionian Sea) - Russo, Tommaso; Bitetto, Isabella; Carbonara, Pierluigi; Carlucci, Roberto; D'Andrea, Lorenzo; Facchini, Maria T.; Lembo, Giuseppe; Maiorano, Porzia; Sion, Letizia; Spedicato, Maria T.; Tursi, Angelo; Cataudella, Stefano (Frontiers in Marine Science, 2017)
The new Common Fisheries Policy (CFP) is designed to represent an appropriate response to the uncertainties and challenges facing the fisheries sector. It also adopts a holistic approach to fisheries management, considering all factors driving fishers’ behavior, and ultimately, the long-term maintenance of living resources. The most reliable way to pursue these aims could be represented by a change in the exploitation pattern, in order to guarantee the sustainability of fisheries without compromising their socioeconomic viability. In this paper, the demersal fisheries of the Ionian Sea (Geographic Sub-area [GSA] 19) were analyzed with respect to their spatial, temporal, economic, and biological characteristics in terms of four key species for fisheries, namely European hake, red mullet, giant red shrimp, and deep-water rose shrimp. Specifically, 1) a quantitative procedure was applied to break down the whole system (including small-scale fleet components) into a series of fishing grounds using input data about fishing efforts; 2) the different fleet segments were defined as a combination of main gear and fishing grounds; 3) the effort and production by fleet segment were derived according to biological samplings of commercial data (Data Collection Framework for the collection and management of fisheries data, DCF), information on localization of nursery and spawning grounds, and expert knowledge; and 4) all this information was used to feed a bioeconomic modelling tool (BEMTOOL), and to explore alternative exploitation patterns. A series of scenarios including the status quo were defined, starting from the actual management approach based on temporal fishing closure. The results showed that significant improvements in the exploitation pattern could be achieved by setting up spatial and/or temporal gear-specific bans of the fishing activity. More specifically, scenarios based on a 3-month fishing ban for trawlers are expected to provide high rebuilding of the spawning stock biomass (SSB) for all target stocks, and at the same time, result in a remarkable reduction of discards. When combined with a seasonal fishing ban for small-scale fleets equipped with nets and longlines, this approach could lead to a significant improvement in all indicators, but especially the SSB of the exploited species.